DEVELOPMENT MODEL OF ADMINISTRATOR COMPETENCE STANDARD OF OIL PALM PLANTATION - Sapruwan, Muhammad (IJER - INDONESIAN JOURNAL OF EDUCATIONAL REVIEW, 2017)
Indonesian oil palm plantation is progressing very rapidly, even it becomes business perspectives in the future. It has high competitiveness in the world market, unfortunately it is not supported by competent human resources in the field of administration. This occurs because of no mapping in the standard of administrators competence of oil palm plantations up to this time. Research and development of this model aims to produce a standard product competence administrators of oil palm plantations. The result of this research can be used to determine the position of human resources to meet the requirements of a competent workforce in objective, valid and reliable way . At conceptual development and empirical testing stages performed a series of feasibility studies, they are ; expert review of experts, the position holders review, linguists review and field trials. The analytical method used are a qualitative and quantitative.The result of the research competence of administrators obtained seven dimensions: accounting, finance, payroll, plant, purchasing, warehousing, and personnel. The highest reliability coefficient test result is on the financial dimension, and the lowest is on the dimensions of the plant.